Navigating personal and disciplinary frontiers: engaging with undergraduate geography students' reflections on their geographical education - Healy, G; Hammond, L (Taylor and Francis, 2024)
In this article, we engage with undergraduate geography students’ reflections on their geography education. We begin by examining the position of geography within education across the British Isles. Following this, we critically consider how geography education is shaped by “the gap” between school and university geography and geographies of education, before reporting on the findings from a survey of 333 undergraduate students studying geography across the British Isles conducted in late 2020. We examine the complex question of who is studying geography at undergraduate level, students’ journeys through their geography degree, and their experiences of personal and disciplinary frontiers in education. We conclude by arguing the importance of educators engaging with students’ “everyday” geographies, and for further research into progress across education phases in geography to co-construct a rich and rounded geographic education.